Design Patterns for Managing Product Life Cycle Information. - Främling, Kary; Ala-Risku, Timo; Kärkkäinen, Mikko; Holmström, Jan (Communications of the ACM, 2007)
The article discusses the use of design patterns for managing product life cycle information. Efforts to make information about products easily accessible during a product's entire lifetime have created an environment that often leads to information overflow in the downstream supply chain. The authors examine object-oriented programming as method of creating computer software that can last longer, as well as the effects of the Internet on the ability to make product information available at all times.